A narrativa mediada e a permanência da tradição: percurso de um anti-herói brasileiro - Luiz Gonzaga Motta (Estudos de Literatura Brasileira Contemporânea)
The article describes a narrative analysis of the song “Faroeste Caboclo”, written by the Brazilian composer Renato Russo. It freely applies the procedures proposed by the Russian narratologist Vladimir Propp in a typical product of the cultural industry to comprehend the narrative of a Brazilian modern anti-hero. The first objective is to observe whether Propp proposals are still valid as procedures for semantic interpretation of a product of the cultural industry (which retain a commercial nature, different from children’s tales in which the Russian author based his procedures). The second objetive tests whether the mediated narrative still keeps an identity with the universal cycle of the hero and the symbolic nature of traditional narratives. The article concludes that mediated narratives are not less authentic: they have been reincorporated into new contexts and re-anchored in new communication supports. They still retain, however, the authentic dramatic models to represent human life.